1997
DOI: 10.1177/0893318997112003
|View full text |Cite
|
Sign up to set email alerts
|

The Acculturation of Immigrants to U.S. Organizations

Abstract: Questionnaires from 277 Muslim immigrants revealed that most were more inclined to retain their original national culture for their private and/or social lives than to adopt the U.S. national culture. In contrast, most accepted U.S. organizational cultures. Collectivism, religious beliefs and practices, gender, education, and years lived in the United States related to acculturation to the U.S. national culture; national acculturation, collectivism, and perceived discrepancy in work cultures related to accultu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
30
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(31 citation statements)
references
References 28 publications
0
30
0
Order By: Relevance
“…The second scale, KEEP, measured respondents' willingness to keep their original culture. Both scales were adopted from Alkhazraji et al (1997) with minor changes to fit the current populations. Responses to ADOPT statements are coded so that a high score indicates high acceptance of the U.S. culture.…”
Section: Cultural Orientationmentioning
confidence: 99%
“…The second scale, KEEP, measured respondents' willingness to keep their original culture. Both scales were adopted from Alkhazraji et al (1997) with minor changes to fit the current populations. Responses to ADOPT statements are coded so that a high score indicates high acceptance of the U.S. culture.…”
Section: Cultural Orientationmentioning
confidence: 99%
“…Following Bhatia and Ram [2001], however, the amount of acculturation-related change observed likely depends on the immigrant group and receiving society in question. Individuals from diasporic groups or religious-based cultural backgrounds may be less willing to emphasize individualism and personal identity, and may resist change either because of perceived expectations from the enclave or religious community [Alkhazraji, Gardner, Martin, & Paolillo, 1997] or because of the perceived superiority of collectivist values (e.g., the familism cherished by many immigrant groups) [Markovic & Manderson, 2002].…”
Section: Social Identity: Individualism and Collectivismmentioning
confidence: 99%
“…Previous studies in ethnically similar populations have reported lower response rates associated with longer questionnaires (see e.g., Alkhazraji et al, 1997). While reducing the size of the questionnaire was one of our concerns, it is important to mention that we derived our measures from a number of phenomenological interviews conducted with Shia youth as part of our exploratory research, and the resulting instrument had been reviewed by members of our population of interest.…”
Section: Discussion Of Resultsmentioning
confidence: 99%